HIGH-THROUGHPUT SCREENING AND DYNAMIC STUDIES OF SELECTED COMPOUNDS AGAINST SARS-COV-2 - BHOWMIK, RATUL; NATH, RANAJIT; SHARMA, SAMEER; ROY, RATNA; BISWAS, RIYA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study was aimed to analyze the inhibitory effect of the drugs used in nanocarrier as well as nanoparticles formulation based drug delivery system selected from PubChem database literature against 3CLpro (3C-like protease) receptor of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) by implementing several in silico analysis techniques. Methods: This paper detailed a molecular docking-based virtual screening of 5240 compounds previously utilized in nanoparticle and nanocarrier drug delivery systems utilizing AutoDock Vina software on 3CL protease to discover potential inhibitors using a molecular docking technique. Results: According to the results of the screening, the top two compounds, PubChem Id 58823276 and PubChem Id 60838 exhibited a high affinity for the 3CL protease binding region. Their binding affinities were-9.6 and-8.5 kJ/mol, indicating that they were tightly bound to the target receptor, respectively. These results outperformed those obtained using the co-crystallized native ligand, which exhibited a binding affinity of-7.4 kJ/mol. PubChem Id 60838, the main hit compound in terms of both binding affinity and ADMET analysis, displayed substantial deformability after MD simulation. As a result of the VS and molecular docking techniques, novel 3CL protease inhibitors from the PubChem database were discovered using the Lipinski rule of five and functional molecular contacts with the target protein, as evidenced by the findings of this work. Conclusion: The findings suggest that the compounds discovered may represent attractive opportunities for the development of COVID-19 3CLpro inhibitors and that they need further evaluation and investigation.